PERBANDINGAN PENGATURAN TANGGUNG JAWAB DIREKSI BUMN (PERSERO) ANTARA INDONESIA DAN JERMAN : Comparison of the Regulations on the Responsibilities State-Owned Enterprises (Persero) Directors between Indonesia and Germany - Meyra Tiara Rizyanka Marsaoleh; Dian Purnamasari (Faculty of Law, Universitas Trisakti, 2026)
The Board of Directors (BoD) plays crucial role as a corporate organs, bearing full responsibility for the management and interests of the company. This study analyzes the comparative regulation of the responsibilities of the BoD of State-Owned Enterprises (Persero) under Indonesian and German law. The research question in this study is how the regulation of the responsibilities of directors of SOEs (Persero) compares under Indonesian and German law. The legal research method used is a descriptive normative legal method, by examining primary legal materials such as Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 19 of 2003 and its amendments concerning SOEs for Indonesian regulations, GmbHG and AktG for German regulations, as well as relevant secondary legal materials. The results of the study and conclusions indicate that there are similarities in the basic principles of the BoD responsibilities, namely the obligation to act prudently and prioritize the interests of the company. The main difference lies in the function of legal protection and insurance for directors, where Indonesian law emphasizes the exemption of directors from liability without personal contribution obligations, while German law limits insurance protection through a self-retention mechanism to strengthen accountability.